Analytical and numerical modeling of elastic moduli for cement based composites with solid mass fractal model. (30th May 2018) - Gao, Yun; Feng, Pan; Jiang, Jinyang
Highlights: The solid mass fractal model describes well pore-solid structure in cement paste. Analytical modeling of elastic moduli is performed using effective medium theory. Numerical modeling of elastic moduli is performed using finite element method. Abstract: Elastic moduli are of the critical parameters in performance design and analysis for cement based composites. As a result of the intrinsic heterogeneity, however, the prediction of elastic moduli remains a practical challenge. In this paper, the solid mass fractal model is applied, which builds up the pore-solid structure of slag-blended cement paste in conjunction with the mercury intrusion porosimetry test. Moreover, the analytical and the numerical modeling of elastic moduli are performed making use of the effective medium theory and the finite element method, respectively. For the sake of validation, the elastic moduli from modeling are compared with those measured from the ultrasonic wave test. Most of all, this paper intends to propose a novel method that predicts well the elastic moduli of cement based composites.